Estrutura da assembleia de peixes em igarapés de pequena ordem de fragmentos florestais em uma matriz de savana, Amazônia oriental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Savannas in the Amazon are restricted to only about 3% of the Amazon basin, and knowledge about fish diversity in these areas is still incipient, which is the least studied group of organisms. Environmental changes generate changes in aquatic habitat, so changes in the fish community are expected over time, but when they do not profoundly affect water quality, some resistance from communities is expected. To determine the composition of the ichthyofauna, three samplings were performed in 13 first and second order streams inserted in forest fragments surrounded by a savannah matrix on the left bank of the lower Tapajós River. May and the last in October 2018. To investigate the effects on the change of environmental characteristics on the taxonomic composition of fish, a set of ten streams from the October 2006 and 2018 samplings were used. A standardized effort protocol was used. A total of 6,094 individuals were collected distributed in 43 species, belonging to 21 families and eight orders, Characiformes and Cichliformes being the most representative orders. The community composition of these streams is different from nearby areas, corresponding to an important set for regional diversity. The intensity and direction of the temporal change of the datasets between 2006 and 2018 were analyzed. Changes in some structural and limnological characteristics of the streams between the years were detected, showing a decrease in the environmental integrity. There was no change in the taxonomic composition of the community. Although fish are able to withstand the current level of environmental degradation on these streams, there are variations in the total abundance of some species-related changes in specific microhabitats, it is likely that changes in the use of streams that intensify the loss of water quality. may lead to diversity losses. Therefore, investigations are needed to quantify this kind of effect and monitor its changes.
Keywords: Peixes neotropicais; Igarapés de cabeceira; Resistência; Biologia; Recursos Florestais e Engenharia Florestal; BIODIVERSIDADE; ECOLOGIA